2020
DOI: 10.1002/uog.22682
|View full text |Cite
|
Sign up to set email alerts
|

VP22.11: Outcomes of radiofrequency ablation for selective fetal reduction in complicated monochorionic pregnancies performed before or after 16 gestational weeks

Abstract: rising from 3.8 g/dL to 12.1 g/dL). After 2 weeks, there was hydrops resolution and a reduction in MCA-PSV discordance. MR performed 3 weeks after IUT showed periventricular leukomalacia (PVL) in the DT, which died at 32 weeks with no consequences for the RT. Case 2: A MC complicated by sIUGR developed TAPS at 23 weeks with reversed-end diastolic flow in the umbilical artery of the DT (stage 3). US revealed cortical hyperecogenicity in the DT. Laser surgery was chosen with resolution of TAPS within 48 hours. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…There were no significant differences in the pregnancy outcomes between the two groups, including the rates of postprocedural complications, termination of pregnancy after RFA, preterm birth, and live birth. In our study, the overall live birth rate was 73.5%, which is similar to the live birth rate reported by previous 3,9,11 studies. The mean gestational age at delivery was 31.0 AE 7.5 weeks in the abdominal needle insertion group and 32.2 AE 5.5 weeks in the dorsal needle insertion group, which are earlier than those in previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…There were no significant differences in the pregnancy outcomes between the two groups, including the rates of postprocedural complications, termination of pregnancy after RFA, preterm birth, and live birth. In our study, the overall live birth rate was 73.5%, which is similar to the live birth rate reported by previous 3,9,11 studies. The mean gestational age at delivery was 31.0 AE 7.5 weeks in the abdominal needle insertion group and 32.2 AE 5.5 weeks in the dorsal needle insertion group, which are earlier than those in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study reported that gestational age at delivery was earlier if RFA was performed after 16 weeks. 9 Additionally, Cox regression analysis in this study showed that gestational age at RFA was at independent risk factor of the duration of pregnancy after RFA.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations